2016
DOI: 10.5562/cca2916
|View full text |Cite
|
Sign up to set email alerts
|

Human DPP III – Keap1 Interactions: A Combined Experimental And Computational Study

Abstract: Kelch-like ECH associated protein 1 (Keap1) is a cellular sensor for oxidative stress and a negative regulator of the transcription factor Nrf2. Keap1 and Nrf2 control expression of nearly 500 genes with diverse cytoprotective functions and the Nrf2-Keap1 signaling pathway is a major regulator of cytoprotective responses to oxidative and electrophilic stress. It was found that the metallopeptidase dipeptidyl peptidase III (DPP III) contributes to Nrf2 activation by binding to Keap1, probably by binding to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Calculated RMSF values show the Phe454–Thr487 loop to be highly flexible. This structural motif is also present in the human orthologue and it is suspected to be the site of the DPP III–Keap1 interaction . The proposed “hinge” region that connects the two domains also proved to be highly flexible, while the inner core of the protein is mostly rigid (Supporting Information Figure S8).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Calculated RMSF values show the Phe454–Thr487 loop to be highly flexible. This structural motif is also present in the human orthologue and it is suspected to be the site of the DPP III–Keap1 interaction . The proposed “hinge” region that connects the two domains also proved to be highly flexible, while the inner core of the protein is mostly rigid (Supporting Information Figure S8).…”
Section: Resultsmentioning
confidence: 89%
“…This structural motif is also present in the human orthologue and it is suspected to be the site of the DPP III-Keap1 interaction. 69 The proposed "hinge" region that connects the two domains 30 also proved to be highly flexible, while the inner core of the protein is mostly rigid (Supporting Information Figure S8). This data agrees well with the B-factors of the crystal structure (Supporting Information Figure S9).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, for the first time, the protein-protein interaction of human DPP III involving the substrate binding region of this enzyme has been demonstrated. Up to date, only hDPP III interaction with the Keap1 protein (Gundi c et al, 2016;Hast et al, 2013) has been described. DPP III binds to Kealch domain of Keap1 via the E 480 TGE 483 motif situated in the flexible loop on the surface of the "upper" domain and remote from the substrate binding site.…”
Section: Analysis Of Protein-protein Interactionsmentioning
confidence: 99%
“…Previously, we have shown that the binding of DPP III to Kelch is a two-step process, which involves separation of the ETGE motif, which is located at the tip of the flexible loop in the upper domain of DPP III, from the protein body and insertion of the loop with ETGE motif into the binding site of the Kelch domain. We showed that the DPP III-R623W variant, in which the ETGE loop is less tightly bound to the protein body, has a substantially higher affinity towards the Kelch domain than the WT [16,17]. In this work, we extended our investigations to some other mutations that either shift the equilibrium process of loop detachment or alter the binding affinity of the ETGE loop of DPP III to the Kelch domain.…”
Section: Introductionmentioning
confidence: 85%